Nigella Sativa Oil Protects Against Aluminium Chloride-Induced Cognitive Impairment Via Modulation of Cholinergic Activity, Brain Neurotransmitter, and Oxidative Stress - Ayodeji Oluwatobi Ojetunde; Abdulwahab Alhassan; Ibrahim Suleiman; Ahmed Sherif Isa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and memory impairment, with no known cure. This study investigated the potential protective effects of Nigella sativa oil (NSO) on aluminium chloride-induced cognitive impairment in Wistar rats. Twenty-four rats were divided into four groups. Group I received 1 ml/kg of distilled water. Groups II-IV were administered aluminium chloride (100 mg/kg). Groups III and IV were co-treated with NSO at 1 ml/kg and 2 ml/kg, respectively. Neurobehavioral assessments (Morris water maze and Y-maze) were performed, followed by biochemical analysis of brain tissues. Aluminium chloride significantly (p < 0.05) impaired spatial learning and memory and decreased the percentage of alternation. It also significantly (p < 0.05) increased acetylcholinesterase level, glutamate concentration, and malondialdehyde level, and decreased antioxidant markers. Meanwhile, Nigella sativa oil (1 ml/kg and 2 ml/kg) significantly (p < 0.05) improved learning ability and spatial memory, and increased percentage alternation in the Y-maze test. Nigella sativa oil also significantly (p < 0.05) decreases acetylcholinesterase, glutamate, and malondialdehyde, and increases antioxidant biomarkers. This study showed that Nigella sativa oil can improve cognitive and spatial learning functions via modulation of cholinergic activity, brain neurotransmitters, and oxidative stress.